First time in the European parliament elections - Bačlija Brajnik, Irena (Družboslovne razprave, 2004)
The first European Parliament elections in the new Member States in Central and Eastern Europe demonstrated a profound paradox in terms of being a feedback process of European integration. At the elite level, the accession tothe European Union has offered political parties and their leaders both new opportunities as well as a new set of issues with the emergence of a significant divide over the meanings of European integration. At the mass level, however, the first European Parliament elections were ignored by a vastmajority of voters. This paper serves as a systematic analysis of the subject. Our objective is three-fold: to explain a lack of interest in the polls, to examine the domestic political dynamics leading to the elections andto consider the implications of the elections for the workings of the enlarged European Union. As for the prospects for European integration, it is important to note that one may no longer assume a supportive cross-party consensus in the new Member States on the EU. Rather, popular antipathy towards the EU is expected to rise
Keywords: Central Europe; Srednja Evropa; Eastern Europe; Vzhodna Evropa; integracija; European Union; Evropska unija; Evropski parlament; election; volitve; political party; politične stranke